An Empirical Appraisal of Electronic Service Quality, Customer Satisfaction and Behavioral Intentions within Online Shopping in South Africa - Maziriri, Eugine Tafadzwa; Chuchu, Tinashe; Rukuni, Tarisai Fritz (Journal of Consumer Sciences, 2023)
Over the years, service quality has been a topic that has continued to garner a lot of interest. This study sought to appraise electronic service quality, customer satisfaction, and behavioral intentions in online shopping in South Africa. A unique conceptual model was developed to investigate the factors that led to customer loyalty, positive word-of-mouth, and ultimately repurchase intention toward goods online. This study aims to determine the influence of e-service quality on customer satisfaction and behavioral intentions in online shopping in South Africa. Non-probability sampling was used to select the participants. A structured questionnaire, based on the conceptual model, was developed and distributed online. A total of 307 usable response questionnaires were collected, and descriptive and regression analyses were conducted using SPSS 27. The major findings indicate that customer satisfaction and positive word of mouth are closely associated. The implication is that marketing practitioners should pay more attention to customer behavior after receiving services.